New forms of human trafficking: global south highlights and local contexts on sexual and labor exploitation - Rodrigues, Anabela Miranda; Guia, Maria João (Springer, 2024)
Chapter 1. “Don't Give Me Moral, but a Social Ideal”: From the Social Condemnation of Prostitution to the Criminalisation of Sexual Exploitation: Pimping and Human Trafficking in the Portuguese Penal Code -- Chapter 2. Cross-Border Organized Crime and Human Rights: The Awfulness of Trafficking in Human Beings. Chapter 3. Combating Human Trafficking in South Africa -- Chapter 4. Human Trafficking Policies in Scandinavia: What Happens When International Obligations Meet National Problem Definitions? -- Chapter 5. Fight Against Human Trafficking in Poland: From Theory to Practice -- Chapter 6. The Silenced Coercion of Voodoo over Nigerian Women Trafficked from West Africa to Europe -- Chapter 7. Transvestites and Transwomen in Human Trafficking for Sexual Exploitation: A Study In Brazil -- Chapter 8. Romania – Trendstetter in European Human Trafficking? -- Chapter 9. Individuals Treated As Nonpersons and the Challenge to Criminal Justice: The Specific Problems Facing Victims of Trafficking in Human Beings -- Chapter 10. Trafficking in Human Beings as an Hourglass Paradigm -- Chapter 11. The Formal Institutions of Control and the Victims of Human Trafficking: From Frequency to Impunity -- Chapter 12. Human Trafficking in Slovenia: Contemporary Issues -- Chapter 13. How Organized is Labour Trafficking? On the Involvement of Organized Criminal Groups in Labour Exploitation -- Chapter 14. Human Trafficking in Brazilian Law: The New Legal Definition -- Chapter 15. Trafficking in Persons vis-à-vis the Recent Jurisprudence of the Inter-American Court of Human Rights: Lessons for Brazil.